ON MASS LOSS FROM EVOLVED MASSIVE STARS - Dorodnitsyn, A. V.; Bisnovatyi-Kogan, G. S. (Одеські астрономічні публікації, 2017)
We consider stationary out flowing stellar envelopes accelerated by a radiation flux pressure. A method is developed describing a spherically symmetric flow in radiational hydrodynamics in regions with arbitrary optical depth (τ ). The solution of the derived system of differential equations is obtained numerically. It proceeds through the singular point, where a velocity is equal to the isothermal sound speed, and satisfies zero temperature and pressure boundary conditions at the infinity. Method is discussed of self- consistent evolutionary calculations for massive stars on the stage of yellow and red supergiants, with a mass loss determined unambiguously.